2009
DOI: 10.1024/0036-7281.151.2.61
|View full text |Cite
|
Sign up to set email alerts
|

Changes in body weight, hematology and serum chemistry in captive plains viscachas (Lagostomus maximus) with presumptive diabetes type II after a diet change

Abstract: Changes in body weight, hematology and serum chemistry in captive plains viscachas (Lagostomus maximus) with presumptive diabetes type II after a diet change We report body weights (BW) and blood and serum analyses for 6 fully mature and 8 not-yet-mature captive plains viscachas before and 3, 6 and 9 months after switching from a low-fi ber, high-energy diet to a high-fi ber, low-energy diet. Initially, body weights, serum glucose, fructosamine and cholesterol levels were above the reference range in the fully… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…This interpretation is supported by elevated fructosamine, glucose, and cholesterol values recorded in animals before the diet change, 34 and implies that cataract is caused by diabetes. This is in accord with literature reports in other rodents e.g.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…This interpretation is supported by elevated fructosamine, glucose, and cholesterol values recorded in animals before the diet change, 34 and implies that cataract is caused by diabetes. This is in accord with literature reports in other rodents e.g.…”
Section: Discussionsupporting
confidence: 57%
“…34 It was suggested that these findings were consistent with (but not necessarily proof of) a non-insulin dependent (type 2) diabetes mellitus.…”
Section: Introductionmentioning
confidence: 48%
See 1 more Smart Citation
“…This comparison indicates that the concentrate diets used in the present study are more digestible than the diets plains viscachas probably have adapted to over evolution. The relevance of maintaining rodents susceptible to diabetic conditions on high‐fiber diets without concentrates has been repeatedly recommended in order to prevent obesity and diabetes, and this not only with respect to viscachas [Gull et al, ; Wenker et al, ] but also for degus [Edwards, ], tuco‐tucos ( Ctenomys talarum ) [Wise et al, ], agoutis ( Dasyprocta spp.) [McWilliams, ], and sand rats [Kalman et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…They are herbivorous [Campos et al, ], with an apparent preference for grasses [Giulietti and Jackson, ; Branch et al, ; Puig et al, ; Bontti et al, ; Pereira et al, ], and have been reported to have a low metabolic rate [Kohl, ]. Nevertheless, their diet in captivity has traditionally contained varied amounts of energy dense feeds, which may trigger diet‐induced diabetes mellitus with cataract formation, similar to degus ( Octodon degus ) [Rübel et al, ; Gull et al, ; Wenker et al, ].…”
Section: Introductionmentioning
confidence: 99%